Incidencia del reportaje en los noticieros en los matinales de la ciudad de Babahoyo - Barahona Guaman, Edison Javier (2019)
At present, being informed of what is happening and happening in our environment and the world has become important and necessary, so various news programs have been created that inform citizens through methods and strategies. Several news programs use the report to inform, due to the way and structure it has to present the development of a topic of interest through the media such as radio and television. The news considered as programs that are dedicated to the dissemination of information content through a space, which can be transmitted through radio and television in order to keep the citizen informed of what is happening in the world, using the necessary resources that they possess depending on the medium in which they are transmitted. The application of the report is necessary for the dissemination of information in the informative spaces called newscasts, due to the fact that it is considered as the complete journalistic genre for its investigative work that it carries out on a topic of interest, and then the events that are presented in detail They understand